Between Opportunity and Vulnerability: Women’s Access to the Creative Economy in the Coastal Village of Taman Ayu - Hulwatul Izmi (POPULIKA, 2026)
Women's participation in the creative economy is a crucial aspect of achieving inclusive local development, particularly in coastal areas that have a high level of exposure to disaster risks. This study aims to analyze women's access to the creative economy sector and identify the opportunities and vulnerabilities they face in the context of disaster risks in the coastal village of Taman Ayu. This research employs a qualitative approach with data collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using the Gender-Sensitive Sustainable Livelihoods Framework, which integrates gender analysis with disaster vulnerability assessment. The findings reveal that women play a significant role in supporting household income and sustaining community livelihoods through creative economy activities; however, their participation remains constrained by limited access to capital, skill development, and institutional support. On the other hand, women's involvement in creative economy activities serves as an adaptive strategy that strengthens the social and economic resilience of coastal communities to disaster risks. Therefore, this study concludes that strengthening women's capacity and improving their access to economic resources through inclusive and gender-responsive programs are essential to promoting resilient and sustainable coastal village development.   Keywords: Women’s Participation; Creative Economy; Gender; Coastal Community; Disaster Risk